EVALUATION EMPOWERMENT OF OFFICER ASSESSORS FOR ASSESSMENT PROGRAM TO PRODUCE SUPERIOR OFFICERS OF THE INDONESIAN NAVY - Aries Sudiarso, R. Madhakomala, Suparno Eko Widodo, Hamidah, Hapzi Ali (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The purpose of this research is to empower appraisal officers who have moral attitudes or behaviors and integrity in producing superior officers of the Indonesian Navy. The research was conducted at the TNI AL Personnel Office, Jl. Cilangkap Jakarta. Based on the scientific literature, this research is an evaluation study of the Kickpatrick Evaluation Model (Level 3, Behavior and Level 4 Outcomes / Impacts). The data were obtained through observation, interview, and documentation instruments as well as using descriptive survey research methods, by means of explanotary and qualitative approaches. On the basis of the principle of developing research that has been carried out "Dapen Persmil TNI AL program, it is expected that officers who carry out the assessment task have the ability to produce superior officers. However, the findings in this study show that how empowerment has not been found is in accordance with the career development program for Indonesian Navy personnel. The findings of this research indicate that the empowerment of appraisal officers who have moral attitudes or behaviors and integrity as organizational assets as Human Capital (HC) if there is no awareness of empowerment as a total supervisor about attitudes or behavior, especially for Indonesian Navy Officers. Because in its implementation, how to empower officers is related to the problem of evaluating officer empowerment whose attitudes and behavior produce superior officers in the Navy.